2010
DOI: 10.1002/pro.444
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of an ionic complementary peptide with a hydrophobic graphite surface

Abstract: Protein adsorption on a surface plays an important role in biomaterial science and medicine. It is strongly related to the interaction between the protein residues and the surface. Here we report all-atom molecular dynamics simulations of the adsorption of an ionic complementary peptide, EAK16-II, to the hydrophobic highly ordered pyrolytic graphite surface. We find that, the hydrophobic interaction is the main force to govern the adsorption, and the peptide interchain electrostatic interaction affects the ads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…In an SGMD simulation, the system undergoes an accelerated systematic motion, which is defined by the local averaging time, t L , while maintaining a desired temperature. Many applications have demonstrated that SGMD simulations have an enhanced conformational search ability (Choudhary & Clancy 2005a; 2005b; Lung et al 2001; Sheng et al 2010a; 2010b; Varady et al 2002; Wu & Wang 2000; 2001; Wu et al 2002). Shinoda and Mikami extended SGMD to the NPT ensemble (Shinoda & Mikami 2001) and later combined it with the rigid body dynamics (Shinoda & Mikami 2003).…”
Section: History Of the Sgmd And Sgld Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In an SGMD simulation, the system undergoes an accelerated systematic motion, which is defined by the local averaging time, t L , while maintaining a desired temperature. Many applications have demonstrated that SGMD simulations have an enhanced conformational search ability (Choudhary & Clancy 2005a; 2005b; Lung et al 2001; Sheng et al 2010a; 2010b; Varady et al 2002; Wu & Wang 2000; 2001; Wu et al 2002). Shinoda and Mikami extended SGMD to the NPT ensemble (Shinoda & Mikami 2001) and later combined it with the rigid body dynamics (Shinoda & Mikami 2003).…”
Section: History Of the Sgmd And Sgld Methodsmentioning
confidence: 99%
“…The enhanced conformational searching ability of SGMD and SGLD are demonstrated by their many applications in protein folding (Lee & Chang 2010; Lee & Olson 2010; Wu & Wang 2000; 2001; Wu et al 2002), ligand binding (Lung et al 2001; Varady et al 2002; Yang et al 2004), conformational transitions (Damjanovic et al 2009; Damjanovic et al 2008a; Damjanovic et al 2008b; Pendse et al 2010), phase transitions (Abe & Jitsukawa 2009; Choudhary & Clancy 2002; Chowdhury et al 2003; Tsuru et al 2010; Wu & Wang 1999), and surface adsorption (Sheng et al 2010a; 2010b). There are several method developments along the same concept of SGLD.…”
Section: History Of the Sgmd And Sgld Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…3) simulation methods were developed for efficient conformational searching and have found many applications for the study of rare events such as protein folding, [4][5][6][7][8][9][10][11][12] ligand binding, 13 docking, 14 conformational transition, [15][16][17] and surface absorption. [18][19][20][21] While SGMD/SGLD can accelerate slow events to an affordable time scale, the perturbation in conformational distribution due to the self-guiding force was not quantitatively understood until recently. 22 A common practice for SGMD or SGLD simulations is to limit the guiding factor to a small range so that the effect on conformational distribution is very small and can be neglected.…”
Section: Introductionmentioning
confidence: 99%